Human Wharton’s jelly mesenchymal stem cells inhibit cytokine storm in acute respiratory distress syndrome in a rat model - Wahyu Widowati; Teresa Liliana Wargasetia; Fanny Rahardja; Rimonta F Gunanegara; Didik Priyandoko; Marisca Evalina Gondokesumo; Ervi Afifah; Cahyaning Riski Wijayanti; Rizal Rizal (Asian Pacific Journal of Tropical Biomedicine, 2022)
Objective: To evaluate the potential effect of human Wharton’s jelly mesenchymal stem cells (hWJMSCs) on acute respiratory distress syndrome in lipopolysaccharide (LPS)-induced rats. Methods: The hWJMSCs (5×104/mL, 5×105/mL, 5×106/mL) were administered to rats on day 1 and day 8 after being induced by LPS (5 mg/kg body weight). TNF-α levels in the lung and IL- 18 and IL-1β levels in the serum were measured using ELISA. In addition, caspase-1 expression in lung tissues was quantified using qRT-PCR, and NF-κB and IL-6 expressions were assessed using immunohistochemistry. Results: The hWJMSCs decreased TNF-α levels in the lung and plasma IL-18 and IL-1β levels. Moreover, the hWJMSCs downregulated the expressions of caspase-1, IL-6, and NF-κB in lung tissues. Conclusions: The hWJMSCs can decrease inflammatory markers of acute respiratory distress syndrome in a rat model and may be further investigated for the treatment of acute respiratory distress syndrome.